Assessing the potential contributionof utilizing vacant lands for urban vegetable production in Barangay Mintal, Davao City - Aligato, Jessi Anne Nakol V.; Hualda, Luis Antonio T. (2017)
Increasing world population leads to the process of urbanization where towns and cities are formed as more people begin living in central areas. Development of residential and commercial buildings decreases the availability of agricultural land in urban areas which may result to a problem on food self-sufficiency and farming activities at the community level. However, remaining vacant lands may be utilized for urban agriculture. The main objective of this study is to assess the potential economic contribution of utilizing vacant and idle lands for urban agriculture in Barangay Mintal, Davao City, Philippines using an affordable and accessible system. In identifying if an area is vacant, Geographic Information System (GIS) software and Google Maps were used. Cost-benefit analysis was conducted for vegetable production and valuation f underutilized land to know which may provide better economic and social benefits. Backyard Gardening and Urban container Gardening were suitable urban gardening methods for the identified vacant lands in the area as based on the GIS results supported by ocular inspection. Using an expensive way of assessing vacant lands and secondary data for making decisions what to plant, direct supply of their demands can make production easier with assistance from the local government units in the city.
Thesis (BS Agribusiness Economics) -- University of the Philippines Mindanao, May 2017